Coinfections and superinfections in critically ill COVID-19 patients in Ecuador: a cross-sectional study of bacterial and viral pathogens - Morales-Jadán, Diana; Muslin, Claire; Viteri-Dávila, Carolina; Vélez-Páez, Jorge Luis; Irigoyen-Mogro, Estefanía Belen; Kyriakidis, Nikolaos C.; Garcia-Bereguiain, Miguel Angel; Rivera-Olivero, Ismar A. (Frontiers in Public Health, 2025)
IntroductionThe COVID-19 pandemic has deeply affected Latin America and Ecuador. Coinfections and superinfections increase the risk of morbidity and mortality in COVID-19 patients. This study examined co-infections and superinfections in critically ill COVID-19 patients admitted to the ICU of a tertiary hospital in Ecuador.MethodsA cross-sectional study was conducted from February to August 2021, including patients with a confirmed SARS-CoV-2 infection. Demographic data, clinical characteristics, and microbiological findings were analyzed to evaluate the presence of coinfections and superinfections.ResultsA total of 24 patients were included, of whom 70.83% (17/24) experienced either coinfection or superinfection. Community-acquired coinfections were identified in 12.5% (3/24) of patients, whereas hospital-acquired superinfections were detected in 58.3% (14/24). The most frequently isolated pathogens were Klebsiella pneumoniae, Staphylococcus aureus, and Enterococcus faecalis. Molecular testing revealed Streptococcus pneumoniae was the most prevalent organism. Bloodstream infections were the most common superinfections, with an attack rate of 92.8% (13/14). The median time from hospital admission to superinfection diagnosis was 5 days. The study also found that 33% (8/24) of patients died, all of whom were men; 62% (5/8) of the patients who died have superinfection. However, infections were not identified as independent predictors of death, given the small cohort size (n = 24) and descriptive statistical design.DiscussionThese findings underscore the importance of robust monitoring of co-infections and superinfections in critically ill COVID-19 patients, especially in resource-limited settings. The high prevalence of these infections highlights the need for continued investment in microbiological surveillance, rapid diagnostics, and antimicrobial stewardship programs to mitigate long-term consequences and address the increasing threat of antimicrobial resistance.